2018
DOI: 10.1371/journal.pone.0196769
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of polycystic kidney disease patients on peritoneal dialysis: Systematic review of literature and meta-analysis

Abstract: BackgroundPolycystic kidney disease (PKD) is the most frequent hereditary cause of chronic kidney disease. Peritoneal dialysis (PD) is often avoided for patients with PKD because of the suspected risk of mechanical and infectious complications. Only a few studies have analyzed the outcome of PKD patients on PD with sometimes conflicting results. The purpose of this meta-analysis was to investigate outcomes of patients with PKD treated by PD.MethodsA systematic review and meta-analysis were performed examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
9
0
9
Order By: Relevance
“…Peritoneal dialysis is often avoided in polycystic kidney disease (PKD) patients because of concerns about limited peritoneal space, peritonitis, and hernias. Recent studies support the feasibility of PD in most PKD patients (109)(110)(111)(112)(113)(114). Despite crowding of the peritoneal space with enlarged cystic kidneys, there is no significant difference between PKD patients and non-PKD patients without diabetes for dialysis adequacy and patient and technique survival.…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 94%
“…Peritoneal dialysis is often avoided in polycystic kidney disease (PKD) patients because of concerns about limited peritoneal space, peritonitis, and hernias. Recent studies support the feasibility of PD in most PKD patients (109)(110)(111)(112)(113)(114). Despite crowding of the peritoneal space with enlarged cystic kidneys, there is no significant difference between PKD patients and non-PKD patients without diabetes for dialysis adequacy and patient and technique survival.…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 94%
“…Les résultats de notre étude rétrospective mono-centrique comportant 30 patients sont favorables à la prise en charge en dialyse péritonéale (DP) des patients PKAD, avec possiblement une sélection des patients PKAD selon le volume des reins lors de leur orientation vers une modalité de dialyse. Nous avons confronté notre expérience aux résultats des deux registres Français de dialyse, le réseau REIN pour l'ensemble des patients dialysés et le registre RDPLF de la dialyse à domicile (années 2000 -2010), qui ont été publiés conjointement en septembre 2017 [1], et à ceux de deux méta-analyses récentes regroupant respectivement 9 et 12 études [5,6], majoritairement rétrospectives, souvent mono-centriques. Ces deux méta-analyses se sont essentiellement intéressées à la survie des patients et à celle de la technique de dialyse ainsi qu'aux infections péritonéales, toutes méthodes de DP confondues.…”
Section: Discussionunclassified
“…Dans les registres Français la prise en charge en DP des patients PKAD est associée à une meilleure probabilité d'accès à la transplantation rénale [1]. Les deux méta-analyses publiées en DP [5,6] regroupant respectivement 882 et 931 patients PKAD montrent des résultats similaires en faveur de la prise en charge en DP de ces patients, en particulier pour la survie (meilleure en cas de PKAD) et la survie de la méthode de dialyse qui n'est pas différente des groupes contrôles (patients non PKAD). Une meilleure survie des patients PKAD en DP est aussi observée dans les registres Français de dialyse [1].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This is another very troublesome extra-renal complication of ADPKD that is very prevalent (Dupont et al 2018 ). A study involving the comparison of renal failure patients with and without ADPKD found the abdominal hernia prevalence of 45% (38/85) and 8% (7/85) in patients with renal failure with and without ADPKD, respectively (Mikolajczyk et al 2017 ).…”
Section: Clinical Manifestationsmentioning
confidence: 99%